Penerapan Pendidikan Nasionalisme Terhadap Perilaku Siswa - Ihya Ulumudin (Bidayatuna, 2020)
This research describes the implementation of nationalism education outside the learning process at MI Bustanul Ulum which is located in the Islamic boarding school of Nurul Islam Laweyan Probolinggo. This research is a qualitative descriptive study and the research subjects are the head of the Madrasah, the teachers for grades IV, V and VI as well as some students from those classes. Researcher collected data using observation, interview and documentation. The result showed first, nationalism education outside the learning process is carried out by habituation, extracurricular activities, and routine activities. The values ​​of nationalism given are responsibility, tolerance, courtesy, willingness to sacrifice, cooperation, mutual cooperation, loving the environment, respecting and appreciating the services of heroes, loving Indonesian culture, and others. Second, the factors supporting the implementation of nationalism education, namely students, parents / family, madrasah and the environment. Third, there are no significant obstacles in the implementation of nationalism education outside of learning.